Narrative and Experiment, Religion and Politics in Terrence Malick's The Tree of Life Journal for Religion, Film and Media - Russell C. Powell (Journal for Religion, Film and Media, 2019)
While most interpretations of Terrence Malick's 2011 The Tree of Life concentrate on the film's theological resonances, I focus here on The Tree of Life's political vision. I locate this vision in the fraught relationship between two influential strands of American religio-political thought, Augustinianism and Emersonianism. The Tree of Life's theological concerns are undoubtedly Augustinian, yet it takes up a similar radical politics as what Emerson did in his best-known essays. The result, I argue, is a cinema of religio-political possibility with important implications for a potential rapproachment between religionists (namely evangelical Christians) and secularists, particularly on the topic of environmental conservation and sustainability.